Enhancing rice productivity in sodic soils of Indo-gangetic plains through improved nursery management practices - Singh, Yash Pal; Mishra, Vinay K; Singh, Dhananjay; Gupta, Rav indra K (The Indian Journal of Agricultural Sciences, 2020)
The management practices for rice cultivation in salt-affected soils are obviously different than those in normal soils and for a short duration variety than those of a medium to long duration variety. Hence, experiment was planned and conducted at Central Soil Salinity Research Institute (CSSRI), Regional Research Station, Lucknow, Uttar Pradesh, India during 2011-12 to 2013-14 (kharif) hypothesizing that the combination of improved nursery management practices and high yielding salt tolerant variety would enhance productivity and profitability of rice in sodic soils. The results revealed that, improved nursery management practices like lower seed density, combined application of organic amendments and inorganic fertilizers in the seed bed (5 t/ha farmyard manures (FYM) followed by 100- 50-50 kg N-P2O5-K2O) and optimum age of seedlings enhanced seedling growth (shoot and root length, number of leaves, leaf area and dry matter) resulting higher grain yield and minimized production cost. Thirty-d-old seedling of salt tolerant variety CSR 36 raised using improved nursery management practices yielded 8.4% and 4.0% higher over 25 and 40d-old seedlings respectively. Salt-tolerant variety CSR 36 grown with improved nursery management options and followed by recommended dose of fertilizers (150-60-40-25 kg N-P2O5-K2O-ZnSO4/ha) in main field, could produce significantly higher grain yield than the yield level achieved using prevailing nursery management practices. This approach of combining cost effective nursery management and crop establishment options for salttolerant varieties can maximize the productivity and profitability of sodic lands in Indo-Gangetic alluvial plains.